Analisis Penggunaan Media Pembelajaran “Tusuk Sate” dalam peningkatan Maharah Istima’: Studi Kasus pada Mahasiswi Semester I STAI Darul Ulum Banyuanyar Pamekasan - Jalaludin Faruk Azhari; Asyhari Zubair; Khoirul Bariyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This research was conducted to analyze the use of sentence stick learning media to improve maharah istima' as an effort to improve maharah istima' abilities. This study uses a qualitative research approach because the data influencing research results are descriptive, while the type of research used in this research is phenomenology. The results of the research found several findings. First, the selection of sentence stick media is used to improve maharah kalam and vocabulary (mufradat). Second, the application of sentence stick media is effective in increasing maharah istima' and vocabulary (mufradat). Third, the motivation to learn and teach students and educators increases. Fourth, efficient learning time. However, several factors hinder the learning process by utilizing sentence stick media as the results of the following research. First, too much focus on the application of sentence stick media. Second, tools and materials cannot be used in the long term. Third, not all materials can use sentence stick media.